What do we know about the future of diets and nutrition? - Sulser, Timothy B.; Ruel, Marie T.; Thilsted, Shakuntala H. (International Food Policy Research Institute, 2025)
Diets continue to evolve and nutrition challenges are changing as diets shift from traditional to more modern ones that are higher in animal-source foods, refined grains, and processed and ultra-processed foods; high in saturated fats, sugar, and salt; and low in fiber.